قرآن مجید میں مذکور کامیاب قائد کی خصوصیات (حضرت سلیمان علیہ السلام کے قصہ کی روشنی میں): Qualities of a Successful Leader Revealed in the Holy Quran (In the Light of Story of Hadrat Sulaiman peace be on him) - Syed Mudassar Ali Gardazi; Hafsa Fathma (FIKR-O NAZAR فکر ونظر, 2024)
To live in a human society and to maintain order and justice in the society, it is necessary to have leadership. The importance of leadership in Islam is clear from this saying of the Holy Prophet ﷺ which is quoted by Imam Abu Dawud in his Sunan. This shows the importance of leadership in Islam and how important is it for any community to have a leader. In the interpretation of this saying of the Holy Prophet, Allama Khattabi says that " This order has been given so that everyone's case remains the same and there came no difference of opinion among them, which causes a quarrel between them. That is, The Holy Prophet even for a temporary matter like travel and companionship, ordered the travelers to appoint one of their own as their leader so that he could manage their affairs. Because if they do not make someone a leader, then their affairs will remain chaotic. Qa'id is an Arabic word for which the words Amir, Khalifa, Imam and Hakim etc. are also used as in the above-mentioned hadith, the word “Ameer” has also been mentioned. And its meaning is explained in “Lisan-ul-Arab”: The one who leads the herd in front is called a leader. The story of Hazrat Sulaiman has been mentioned about seventeen times in the seven surahs of the Holy Qur'an and the kingdom & the government that was given to Him has not been given to anyone else, which is also mentioned in many hadiths. You were also the ruler over humans, jinn and all animals & birds at the same time. What attributes of a successful leader do we find in His story? In this article we will try to describe them in detail. You were given special understanding by Allah, which is mentioned in Surah Al-Anbiya. In this paper, an attempt will be made to write down the qualities of a successful leader in the light of this story and what lessons can be learned from them for today's world? And in today's era, how can these attributes be created in oneself? What can be its contemporary application? An attempt will be made to answer these questions in it.